Low Temperature and High Vapour Pressure Deficit Risks to Cool Season Crops in the Sub-tropics - Ram, Daya; Singh, Phool (Annals of Arid Zone, 2016)
Low temperature and high vapour pressure deficit risks has been made by using cumulative percentage frequency distribution method for judicious crop planning in cool season on the basis of 24 year (1971.72 to 1593-94) meteorological data for Hisar, India. During the period, January 1 to 28, the risk of